Design and Manufacturing Technology of High Speed Milling Cutter for Aluminum Alloy. (2017) - Chang, Hongbin; Li, Suyun; Shi, Runping
Abstract: Base on the development practice of carbide milling cutter used for high speed machining of aluminum alloy, through the empirical analysis of the failure mechanism of milling cutter, and combined with the cutting performance of high strength aluminum alloy and the stress strain characteristics of cutter on high speed condition, the design principle, manufacture and using technology of carbide milling cutter for high speed machining of aluminum alloy are discussed in detail.